Association between oral health behavior and chronic diseases among middle-aged and older adults in Beijing, China - Dan Guo; Zhenyu Shi; Yanan Luo; Ruoxi Ding; Ping He (BMC, 2023)
Abstract Objectives To evaluate the association between oral health behavior and multiple chronic diseases among middle-aged and older adults. Methods We obtained data of the Beijing Health Service Survey and used multivariate logistic models to estimate the association between oral hygiene behavior and the risk of chronic diseases. Results The risk of any chronic diseases (OR = 1.27, 95% CI: 1.18-1.37), cardiovascular diseases (CVD, OR = 1.30, 95% CI: 1.21-1.39), and endocrine or nutritional metabolic disorders (OR = 1.11, 95% CI: 1.01-1.22) was higher in those who with poor oral health behavior. There was no significant correlation between oral health behavior and the risk of diseases of the musculoskeletal, respiratory, digestive, and genitourinary systems. Conclusions Poor oral hygiene practices were associated with higher risk of chronic diseases, CVD and diabetes mellitus (DM) among middle-aged and older adults. These findings motivate further studies to evaluate whether improved oral health behavior may prevent the incidence of chronic diseases.